Hypertension, diabetes and cognitive impairment among elderly - Chintya Putri Erlianti; Indang Trihandini (International Journal of Public Health Science (IJPHS), 2022)
Though the most commonly known risk factor of cognitive impairment is advancing age, hypertension and diabetes are often associated with the acceleration of cognitive decline. This study aimed to identify the relationship of these conditions with cognitive impairment among Indonesian elderly. This study was conducted cross-sectionally using data from the fifth wave of Indonesia family life survey (IFLS5). Cognitive impairment was measured through the modified Telephone Interview for Cognitive Status instrument in IFLS5. Hypertension, diabetes, and control variables were obtained from the answers given by the survey respondents. The final model of the multivariate analysis revealed an interaction between chronic diseases and physical activity in affecting the risk of cognitive impairment. The odds of cognitive impairment in physically less active pre-elderly and elderly with only hypertension and only diabetes, compared to those with no history of illness, are 1.14 (95% CI=0.88–1.48) and 2.55 (95% CI=1.04–6.26) respectively. These results suggested that increasing physical activity can help to reduce the risk of cognitive impairment in elderly, as well as pre-elderly, with hypertension, diabetes, or both conditions. Further longitudinal studies are needed to clarify the causal relationship.